Internal tax competition: does this result in economic and investment growth? - Paientko, Tetiana; Oparin, Valeriy; Sarnetska, Yana (Wewnętrzna konkurencja podatkowa: wzrost gospodarczy i inwestycyjny, 2020)
The purpose of the article is to assess the impact of tax competition at national level on economic growth and capital formation. The internal tax competition was considered from the point of view of fiscal decentralisation. The tax revenue decentralization ratio and revenue decentralization ratio are used in this paper as independent variables in panel regression analysis. As dependent variables, GDP per capita growth and capital formation growth were used. Analysis was conducted on a sample of 26 countries. The results of the analysis showed that international tax competition between countries has a greater effect on GDP per capita and capital formation than tax competition within the country. However, this is not due to the nature of tax competition, but to the fact that not all countries use the potential of tax competition within the country. The direction for further research is to analyze the impact of fiscal decentralization on the effectiveness of governments and economic growth in different groups of countries
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 1, s. 23-34
Keywords: tax competition; fiscal decentralization; GDP per capita; capital formation; konkurencja podatkowa; decentralizacja fiskalna; wzrost PKB na mieszkańca; akumulacja kapitału